Strengthening Music Learning at SMKN - Sulistyowati, Ratih; Munte, Alfonso; Silipta, Silipta; Rudie, Rudie (LP2M of Institute for Research and Community Services - UIN Walisongo, 2022)
The Community Engagement (PkM) of the Faculty of Teacher Training of Christian Education choosing the topic is because: Firstly, the author considers SMKN 1 Pulang Pisau to be a potential high school for activities because their Principal is an arts graduate. Second, the school has complete musical equipment as far as the author is concerned. Third, the location and venue of SMKN 1 Pulang Pisau is spacious and adequate as a location for activities. Fourth, the school was able to command all secondary school principals to send representatives of teachers who had taught in the cultural arts department. We explored creative strategies through an ensemble approach in interfaith music learning after reinforcement and/or empowerment. The implementation method in PkM that we have done is Asset Based Community Development (ABCD) method with implementation stages through discovery, dream, design, define and destiny. Our PkM team evaluated the implementation and sustainability of the program at SMKN 1 Pulang Pisau for 4 days. As a result, the beneficiaries were able to plan, select methods, and implement Cultural Arts learning, with music specifications through an ensemble approach. The ensemble as a national music landscape is able to produce musical creativity and resonant rhythms through materials around the beneficiary schools. For example, gallons, bamboo, and wood.